1987
DOI: 10.1111/j.1365-2044.1987.tb03082.x
|View full text |Cite
|
Sign up to set email alerts
|

Memory of cardiac anaesthesia

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

1988
1988
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(16 citation statements)
references
References 20 publications
(1 reference statement)
1
13
0
2
Order By: Relevance
“…Surgical procedures typically identified as belonging to this category are cardiac, obstetric and multiple trauma surgeries [28]. Patients undergoing cardiopulmonary bypass have reported an awareness incidence from 1.1-23% [33,34]. The incidence of awareness related to obstetric anesthesia ranges from 0.4-1.3% [29,35,36].…”
Section: Risk Factormentioning
confidence: 99%
“…Surgical procedures typically identified as belonging to this category are cardiac, obstetric and multiple trauma surgeries [28]. Patients undergoing cardiopulmonary bypass have reported an awareness incidence from 1.1-23% [33,34]. The incidence of awareness related to obstetric anesthesia ranges from 0.4-1.3% [29,35,36].…”
Section: Risk Factormentioning
confidence: 99%
“…Finally, it has been reported that patients can comply postoperatively with instructions given during surgery for simple motor behaviors (Bennett, Davis, & Giannini, 1985;Goldmann, Shah, & Hebden, 1987), and even respond positively to therapeutic suggestions (Evans & Richardson, 1988;Furlong, 1990;Pearson, 1961). Reports such as these have kept ,alive the question of whether intraoperative events may be encoded in memory and influence postoperative experience, thought, and action, despite adequate surgical anesthesia.…”
mentioning
confidence: 99%
“…Patients undergoing balanced anesthesia for cardiac surgery using benzodiazepines, moderate-dose fentanyl (10-15 mcg/kg), isoflurane (end-tidal concentrations 0.5%-1.5%) during anesthetic maintenance and IV propofol infusion (2-6 mg/kg/hr) during and after CPB reportedly have a relatively low incidence of awareness (0.3%; 95% CI, 0.09% to 1.19%) 20 compared with patients in the past who underwent cardiac surgery with high-dose opioid anesthesia supplemented by low dose halothane or nitrous oxide (23%; 95% CI, 11.8% to 40.9%). 22 An important caveat, apart from the wide confidence interval of the estimate, is that 0.3% was probably an underestimate because patients were only interviewed once at 18 hours postoperatively; 20 other studies have found that many patients only remember or report awareness at subsequent postoperative interviews. 18,21,23-26 While the incidence of awareness with high-dose opioid anesthesia is likely to be high, 23% is probably an over-estimate because only 30 patients were included in this study and five of the seven patients who recalled intraoperative events required hypnosis to reveal these memories.…”
Section: Intraoperative Awarenessmentioning
confidence: 98%
“…18,21,23-26 While the incidence of awareness with high-dose opioid anesthesia is likely to be high, 23% is probably an over-estimate because only 30 patients were included in this study and five of the seven patients who recalled intraoperative events required hypnosis to reveal these memories. 22 The potential problem with high-dose opioid anesthesia is that maintenance of unconsciousness is unpredictable. 27 Studies have shown that during opioid anesthesia perception and cortical processing of auditory information may not be suppressed completely.…”
Section: Intraoperative Awarenessmentioning
confidence: 99%